EX-OFFENDER REINTEGRATION IN CONFLICT-AFFECTED AREAS OF NIGERIA: PUBLIC PERCEPTIONS, POLICY CHALLENGES, AND SOCIAL INFLUENCES IN MADAGALI AND GWOZA - TAKUR’AMA NEVISON ZIDON; ROGERS ROLAND WAZAKARI; SHARON EMMANUEL NTASIRI (International Studies Journal)
Reintegrating former offenders into society is a global challenge due to its potential impact on recidivism and the associated burden on the criminal justice system and society. The aspiration to lead a fulfilling and meaningful life is a universal goal, irrespective of one's background. However, for offenders released from correctional institutions, re-entry into society can be fraught with significant challenges. These individuals often face socio-cultural, economic, and personal obstacles that can hinder a crime-free lifestyle and the re-entry process itself. In light of this context, our study aims to examine the public perceptions and attitudes toward ex-offender reintegration in Madagali and Gwoza and the political and social factors influencing community acceptance of ex-offenders in the study area. The study adopts social identify theory and boundary theory as the theoretical framework. The study used quantitative method of data analysis for the study. The study discovered that there is negative public perceptions and attitudes toward ex-offender reintegration in Madagali and Gwoza and involvement of political and social factors influencing community acceptance of ex-offenders in Madagali and Gwoza. The study recommends critical need for awareness programs that challenge the perception of ex-prisoners as perpetual criminals. Highlighting the success of Nigerian Correctional Service rehabilitation programs through community outreach in villages, markets, religious centres, and media could foster greater public understanding of the reintegration process and its benefits.